Alternatives for Designing Augmentative and Alternative Communication Systems for People with Disabilities and Older Adults - Jadán-Guerrero, Janio (2023)
Augmentative and Alternative Communication Systems (AACS) provide a variety of forms of expression used to improve the communication skills of people with disabilities and/or older adults. These systems consist of physical or digital communicator boards that use pictograms to represent an object, a person or an action. The objective of this article is to analyze some easy-to-implement alternatives of SAACs systems, including low-cost digital resources such as websites and Apps; as well as both high devices such as virtual assistants, AI chatbots like GPT, and tangible interfaces. The research analyzes the difficulties that older adults have in activities of daily living, and a proposal is presented that allows to adapt in a dynamic and scalable way. The prototypes generated allowed us to identify some strengths and weaknesses of the possible solutions. These results provide an opportunity for technology designers to take on board the recommendations and use them to design more robust systems adapted to their environment.